2019
DOI: 10.3168/jds.2018-15416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing soybean meal with raw or extruded blends containing faba bean or lupin seeds on nitrogen metabolism and performance of dairy cows

Abstract: faba bean, but tended to be higher with lupin. Milk yield was increased by 2.6 kg with faba bean blend extruded at 140°C compared with faba bean blend extruded at 160°C. Milk fat and milk protein concentrations were decreased by 3.1 and 2.3 g/kg, respectively, with lupin blends compared with soybean meal. Nitrogen partitioning between milk, feces, and urine did not change. Nitrogen apparent digestibility decreased by 3 g/100 g of N between faba bean blend extruded at low and at high temperatures. The content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
3
14
3
1
Order By: Relevance
“…The experimental concentrate consisted of 90 to 10% blends (raw basis) of fava bean (Vicia faba) and linseed. Linseed was added to benefit from the effects of its high lipid content on the extrusion conditions of fava bean (Mendowski et al, 2019). The blends were distributed either raw (RW), or extruded at an expected output temperature of 140°C with different conditions of pretreatment.…”
Section: Animals Experimental Design and Dietsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental concentrate consisted of 90 to 10% blends (raw basis) of fava bean (Vicia faba) and linseed. Linseed was added to benefit from the effects of its high lipid content on the extrusion conditions of fava bean (Mendowski et al, 2019). The blends were distributed either raw (RW), or extruded at an expected output temperature of 140°C with different conditions of pretreatment.…”
Section: Animals Experimental Design and Dietsmentioning
confidence: 99%
“…The increase in temperature within the extruders occurred by self-heating as a result of the applied compression and shear forces, without any external thermal energy supply. Based on an analysis of the literature, in vitro and in situ experiments on the blends (Chapoutot et al, 2016(Chapoutot et al, , 2018 (Mendowski et al, 2019), the target temperature of 140°C was previously shown to decrease the ruminal effective degradability of N without impairing its intestinal digestibility.…”
Section: Extrusion Conditionsmentioning
confidence: 99%
See 3 more Smart Citations